2014
DOI: 10.1186/1471-2334-14-219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and antifungal susceptibility profiles in causative agents of sporotrichosis

Abstract: BackgroundSporotrichosis is a chronic subcutaneous mycosis of humans and animals, which is typically acquired by traumatic inoculation of plant material contaminated with Sporothrix propagules, or via animals, mainly felines. Sporothrix infections notably occur in outbreaks, with large epidemics currently taking place in southeastern Brazil and northeastern China. Pathogenic species include Sporothrix brasiliensis, Sporothrix schenckii s. str., Sporothrix globosa, and Sporothrix luriei, which exhibit differing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
115
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 52 publications
(122 reference statements)
5
115
0
9
Order By: Relevance
“…However, recent reports demonstrated that these drugs are less potent against S. brasiliensis isolates, which have high minimum inhibitory concentration (MIC) values in vitro for these antifungals (Ottonelli Stopiglia et al, 2014;Rodrigues et al, 2014;Borba-Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent reports demonstrated that these drugs are less potent against S. brasiliensis isolates, which have high minimum inhibitory concentration (MIC) values in vitro for these antifungals (Ottonelli Stopiglia et al, 2014;Rodrigues et al, 2014;Borba-Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In most of these cases, morphological correlates of phylogenetic species were not observed until it was possible to sort strains into the various cryptic species, only then were the phenotypic differences recognized. For example, with Sporothrix species, after phylogenetic species and populations had been identified, tests of antifungal drug susceptibility found associations between genotype and phenotype that could be used to predict therapeutic outcomes (Rodrigues et al 2014).…”
Section: Population Geneticsmentioning
confidence: 99%
“…Four species of the Sporothrix complex have been reported as causal agents of sporotrichosis: S. brasiliensis, S. globosa, S. schenckii s. str., and S. schenckii luriei (Rodrigues et al, 2014). S. pallida and S. mexicana are mainly environmental but may also be potentially pathogenic to humans and other mammals.…”
Section: Introductionmentioning
confidence: 99%